Impetigo: green light for essential oils-based natural treatments but not self-formulated - Maura Di Vito; Stefania Garzoli; Sara Guerrera; Domiziana Coggiatti; Debora Talamonti; Domenico Tarantino; Lidia Di Cerbo; Giulia Lombardini; Marcello Pani; Scilla Pizzarelli; Francesca Bugli; Maurizio Sanguinetti (Nutrimentum et Curae)
Staphylococcus aureus and Streptococcus pyogenes are microbial agents of bullous and non-bullous impetigo, respectively. Treatments are based on both topical and oral antibiotics. Adverse effects and the selection of resistant strains are the main drawbacks of the therapy. Essential oils (EOs) could be good candidates for new therapy.